1999
DOI: 10.1007/pl00009634
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic end-to-end aortobifemoral bypass with reimplantation of the inferior mesenteric artery

Abstract: Laparoscopic IMA reimplantation during laparoscopic aortobifemoral bypass is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Dion et al 14 reported IMA reimplantation in a porcine model. In a preliminary study we demonstrated that laparoscopic reimplantation of the IMA in six cadavers was feasible (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Dion et al 14 reported IMA reimplantation in a porcine model. In a preliminary study we demonstrated that laparoscopic reimplantation of the IMA in six cadavers was feasible (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in our modified procedure is that the "peritoneal apron" is totally created from a right-sided intraabdominal approach and made shorter, which is less time-consuming. 2 The posterior retroperitoneal dissection we used to do through trocar 5 proved tedious. Moreover, we noted that this dissection also caused the ureter to be lifted up along its entire length, with potential adverse effects, eg, ischemic stricture, leading to early transient postoperative hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Like some other surgical teams [1, 7], we performed initial experimentN studies on animals, beginning in 1996, to learn more about the laparoscopic surgical technique and gain more familiarity with the main difficulties associated with the transperitoneal, retroperitoneal, and thoracic approaches [2,4,9,13]. At the same time, we developed taparoscopic vascular instruments that were designed to solve the specific problems that we had encountered when performing these new procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The mean postoperative hospital stay was 6 days (range, [3][4][5][6][7][8][9][10][11][12][13], and six of the eight patients left the hospital on or before day 6.…”
Section: Cadaver Studymentioning
confidence: 99%
See 1 more Smart Citation